Qur'ani literacy of talaq verses and reference as an effort to increase legal awareness - Dodi Alpiyendra; Hidayatullah Ismail (Privietlab, 2026)
This research is based on the widespread practice of divorce and reconciliation that are not in accordance with the provisions of sharia and positive law, such as divorce outside the court, reconciliation without registration, and ignorance of the iddah period and women's rights, which reflect the weak Qur'anic literacy of family law verses, especially QS. al-Baqarah 229–232 and QS. at-Talaq 1–2. This library research examines tafsir books, works of classical and contemporary scholars, laws and regulations, as well as journal articles, national books, and empirical studies with an analytical-descriptive approach to interpret the meaning of the verses and their relevance to modern legal practice in Indonesia. The results of the study indicate that Qur'anic literacy plays a significant role in increasing legal awareness in Muslim society, encouraging compliance with court procedures, the importance of official registration, avoiding emotional divorce, and strengthening household ethics to prevent the abuse of divorce and minimize post-separation conflict. The integration of Qur'anic literacy with modern legal literacy ultimately forms a family law culture that is orderly, fair, and in harmony with maqāṣid al-syarī'ah. Thus, strengthening Qur'anic literacy becomes a strategic step in fostering obedience to the rules regarding divorce and reconciliation.